2015
DOI: 10.1021/es505975h
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functionality of Rural Water Services in Developing Countries: A System Dynamics Approach to Understanding the Dynamic Interaction of Factors

Abstract: Research has shown that sustainability of rural water infrastructure in developing countries is largely affected by the dynamic and systemic interactions of technical, social, financial, institutional, and environmental factors that can lead to premature water system failure. This research employs system dynamics modeling, which uses feedback mechanisms to understand how these factors interact dynamically to influence long-term rural water system functionality. To do this, the research first identified and agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…A similar set of feedback mechanisms can be found to exist in a recent study on community-led water service management programs in Central America by Davis [39], where community satisfaction and payment were found to either enable or prohibit project success. In agreement with Willetts' feedback structure, in a study using the input from water sector experts, Walters and Javernick-Will [40] found that the most influential feedback loop included water system functionality, community financial support and effective management. Thus, a unifying aspect shared between these aforementioned feedback loops identified in the literature, and one which we will maintain within our dynamic hypothesis of CBM-service dynamics, appears to be the importance of community satisfaction and involvement as a driver of payment for the proper maintenance of the water system.…”
Section: Cbm: Service Dynamicsmentioning
confidence: 57%
“…A similar set of feedback mechanisms can be found to exist in a recent study on community-led water service management programs in Central America by Davis [39], where community satisfaction and payment were found to either enable or prohibit project success. In agreement with Willetts' feedback structure, in a study using the input from water sector experts, Walters and Javernick-Will [40] found that the most influential feedback loop included water system functionality, community financial support and effective management. Thus, a unifying aspect shared between these aforementioned feedback loops identified in the literature, and one which we will maintain within our dynamic hypothesis of CBM-service dynamics, appears to be the importance of community satisfaction and involvement as a driver of payment for the proper maintenance of the water system.…”
Section: Cbm: Service Dynamicsmentioning
confidence: 57%
“…Future research should focus on weighting the individual elements of a sanitary survey inspection to identify whether some elements have a higher contribution to risk. Such weighting could use an expert opinion or tools such as decision trees or system dynamics approaches to understand the interactions between hazards [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…A study protocol for the workshops and data collection was reviewed and approved by the University of Colorado's Institutional Review Board (IRB # 17-0292) and all participants gave their informed consent for inclusion before they participated in the workshops. Building upon participatory system dynamic methods [55][56][57][58], this work used a 'Factor Mapping' workshop format to elicit knowledge about factor interaction and dynamics as developed by Walters et al [59][60][61][62]. The GMB approach provided a structured process for engaging knowledgeable stakeholders in discussions around complex problems [46,63,64].…”
Section: Methodsmentioning
confidence: 99%
“…Next, the CLD is analyzed using Vensim System Dynamics software to identify all possible unique feedback loops that begin and end at the factor of interest (e.g., Service Sustainability) [74]. Finally, to be able to infer which of the feedback loops are most likely to drive system behavior, each loop is quantified by averaging the strength of all the influences between each factor in the loop [59] (Equation (1)). This creates a 'normalized score' for each feedback loop.…”
Section: Methodsmentioning
confidence: 99%